Conceptualizing English academic writing via verbal and manual metaphors - Jun Zhao (Ibérica, 2009)
As a powerful cognitive tool, metaphor is used in the educational setting to simplify abstract knowledge for learners. Gesture, the material carrier of thought, can represent abstract concepts in a visual mode. Speakers tend to draw on multimodal resources to make use of both verbal and manual metaphors for expository purpose. This article analyzes metaphorical expressions and gestures of four ESL (English as Second Language) composition instructors to probe how both verbal and manual metaphors are used in the educational discourse to concretize abstract concepts of EAP writing (English for Academic Purpose) to second language writers. Gestures are significant in comprehending the metaphorical sense of verbal utterances.